CALCIUM EXCHANGES BETWEEN SEDIMENTS AND WATER IN SOME CULTURE PONDS WITH STRESS ON CARBONATE AND BICARBONATE ALKALINITIES - Ramamirtham, C P; Dinesh Babu, A P (Indian Journal of Fisheries, 2011)
Calcium is an essential element which should be present in the environment for life activities of organisms. Greenway Peter (1983) stated that marine decapods lose their 90% of body calcium during ’ecdysis’, and calcification of new exoskeleton is achieved predominantly with the cakium absorbed from seawater.